Way Forward - Mohd Azlan, Jayasilan; Wong, James; Chin, Sing Yun (UNIMAS Publisher and Wilmar Plantations Sdn Bhd, 2023)
Agricultural expansion is one of the main drivers of deforestation, biodiversity losses, and environmental degradation across the regions of Borneo (Gaveau et al., 2016). Oil palm monocultures support a low account of species diversity mainly due to the absence of forest vegetation and reduced heterogeneity. Thus, forest remnants and HCV forests in oil palm plantations such as Bukit Durang are of great conservation importance and managed accordingly.